Changes in thermophysical and thermomechanical properties of thermally treated anisotropic shale after water cooling. (1st November 2022) - Guo, Yide; Li, Xibing; Huang, Linqi
Highlights: The response of thermally treated shale after water cooling was studied experimentally and numerically. Anisotropy of static and dynamic uniaxial compression strength of shale after thermal treatment and water cooling increased. Static and dynamic uniaxial compression strength response mechanism of shale after thermal treatment and water cooling were explained. Applications and challenges induced by water cooling in deep shale gas extraction were proposed. Abstract: Shale gas has become the development focus of many countries recently for its strategic importance, and the deep shale gas extraction is becoming a priority worldwide. Water-based drilling and fracturing fluid can inevitably lead to an intense heat exchange on deep high-temperature shale reservoirs, thus understanding the changes in thermophysical and thermomechanical properties of deep shale reservoirs after being subjected to water cooling is essential. In this present work, the changes in thermophysical and thermomechanical properties of thermally treated shale specimens (25–200 ℃) with five kinds of bedding plane inclinations (BPI) of 0°, 30°, 45°, 60° and 90° after water cooling are researched in the lab. Results illustrate that as temperature increases, the density and P-wave velocity obviously decrease and the porosity increase for shale specimens with the five different BPI after thermal treatment and water cooling. Dynamic uniaxial compression strength of all the specimens after thermal treatment and water cooling decreases gradually with increasing temperature, while the static one increases except for specimens with the BPI of 60°. The dynamic and static strength anisotropy of specimens became more obvious with increasing temperature, but the treatment temperature does not act well in changing the anisotropic evolution trend under the two conditions. In the end, the overall response of anisotropic shale after thermal treatment and water cooling is discussed by the results of scanning electron microscope (SEM) and ABAQUS numerical simulation, and the mechanism of dynamic and static strength response is systematically revealed. The findings are hoped to provide theoretical guidance and technical support for the deep shale gas extraction.